On Charges of Treason: The High Treason Case against the Afrikaans Broadcasters of Radio Zeesen after the Second World War - Kleynhans, Suné (Scientia Militaria - South African Journal of Military Studies, 2024)
While the Second World War was characterised by battles and intelligence networks, it also involved cases of treason and military legal processes – and South Africa was no exception. The South involvement in the war produced high treason cases, but trials of those historical figures who worked “behind the scenes” are occasionally neglected within academic literature on the South African history surrounding the Second World War. An example of such is the case of high treason of four Afrikaner men accused of broadcasting propaganda from Radio Zeesen to South Africa in Afrikaans, with the aim of jeopardising the South African war effort. This propaganda was carried out strategically within the context of existing Afrikaner resistance against participation in the war. The four accused were SE Holm (Sidney Erich Holm) (Michael Johannes Pienaar). This article focuses on the trials of the four men accused as a series of lesser-known cases in South African history. The aim of the article is to provide a historical narrative of the cases. After providing the necessary contextualisation, the positions of the prosecution and defence, as well as the verdicts of the trials will be outlined. The objective of this article is not to offer a detailed analysis of the criminal justice procedure or the laws surrounding the cases, but rather to make a historiographic contribution to an overlooked aspect of South African history.